A cross‐sectional study of implicit rationing of care in publicly funded nursing homes in Shanghai, China. (26th October 2021) - Zhang, Huimin; Peng, Zixuan; Chen, Qianqian; Liu, Wenwei
Abstract: Aims: To investigate the level of implicit care rationing and its association with training needs in nursing homes in Shanghai, China. Background: Nursing homes in Shanghai are confronted with a lack of care resources. Implicit care rationing can emerge due to inadequate training of care workers. Methods: A cross‐sectional survey was conducted between 10 September and 17 November 2020. A total of 374 care workers from 16 randomly were selected nursing homes from each of the administrative districts participated the surveys. The Basel Extent of Rationing of Nursing Care‐Nursing Home instrument and the training needs analysis were adopted to measure implicit care rationing and training needs, respectively. Multiple regression techniques were used to explore the factors associated with implicit care rationing. Results: Activities related to social care, documentation and activation/rehabilitation (mean rating = 2.8, 1.89 and 1.93 respectively) were mostly likely to be rationed. Training needs of activities of daily living (ADL), activation/rehabilitation and documentation were significantly related to their implicit rationing (β = 0.864, 0.21 and 0.166, respectively, p  < .01). Conclusion: Training needs are crucial determinants of implicit care rationing. Implications for nursing management: Quality control systems are needed to ensure care comprehensiveness. The current training system should be re‐designed according to results of training needs analysis.